Europe's burden promoting good governance across borders - Mungiu-Pippidi, Alina 1964- (Cambridge University Press, 2020)
The EU is many things: a civilization ideal to emulate, an anchor of geopolitical stabilization, a generous donor and a historical lesson on cooperation across nations. A fixer of national governance problems, however, it is not. In this book, Mungiu-Pippidi investigates the efficacy of the European Union's promotion of good governance through its funding and conditionalities both within EU proper and in the developing world. The evidence assembled shows that the idea of European power to transform the quality of governance is largely a myth. From Greece to Egypt and from Kosovo to Turkey, EU interventions in favour of good governance and anti-corruption policy have failed so far to trigger the domestic political dynamic needed to ensure sustainable change. Mungiu-Pippidi explores how we can better bridge the gap between the Europe of treaties and the reality of governance in Europe and beyond. This book will interest students and scholars of comparative politics, European politics, and development studies, particularly those examining governance and corruption